PENGEMBANGAN SOAL EVALUASI PEMBELAJARAN MENGGUNAKAN WORDWALL PADA MATERI SIKLUS AIR - Adinda, Aura; Syahiril Anwar, Wawan; Abdul Gani, Resyi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to develop learning evaluation questions using wordwalls on water cycle materials to determine the feasibility of the product. This research was carried out at SDN Batutulis 3 Bogor in May 2024. It was carried out in class V-C for the 2023/2024 academic year with 20 students. The instruments used in this study consisted of expert validation sheets, student response questionnaires, and teacher response questionnaires to learning evaluation questions using wordwalls on water cycle materials. This data analysis technique consists of qualitative data on the results of interviews and quantitative data on expert validation, student responses, and teacher response questionnaires. The results of the study showed that the learning evaluation questions using wordwalls in class V-C SDN Batutulis 3 Bogor in learning based on the average assessment of media expert validation were 93.3%, the average validation score of linguists was 100%, the average validation score of material experts with criteria was 99%, the results of the validation were included in the category of